(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Depression, a complex and prevalent mental health disorder, remains a challenge for psychiatric intervention. Globally affecting about 5% of adults, depression manifests with gender bias, more prevalent in women. Accompanied by adverse cognitive patterns and the potential for disruptive behaviors, innovative approaches like acupuncture and yoga have emerged. Acupuncture and yoga converge to address both physiological and psychological dimensions of depression. Acupuncture’s equilibrium establishment through vital energy flow, Qi, complements yoga’s mind-body connection, forming a comprehensive approach. Studies substantiate yoga’s efficacy against standard care, including positive outcomes in chronic back pain and prenatal care. Diverse forms of yoga, like Kirtan Kriya and Iyengar yoga, show mood improvements across intensities, with Sudarshan Kriya further alleviating depression, anxiety, and stress. Acupuncture’s potential is evident, as electro-acupuncture (EA) complements anti-depressants. EA matches Fluoxetine’s effects and shows potential in the initial treatment phases. Dense cranial electro-acupuncture stimulation (DCEAS) reduces depression scores with unique mechanisms. Acupuncture’s influence on neurotransmitters and neural pathways underpins its benefits. Neurobiologically, acupuncture modulates corticostriatal connectivity and serotonin receptor expression, contributing to mood improvement. Yoga regulates neurotransmitters, cortisol, and neuroplasticity, enhancing holistic well-being. Acupuncture and yoga’s neurobiological parallels offer potential for mood regulation.